Relation between exhaled nitric oxide and left ventricular performance in chronic hemodialysis patients. (12th September 2013) - Ansarin, Khalil; Toufan, Mehrnoush; Namdar, Hossein; Etemadi, Jalal; Habibzadeh, Afshin; Valinejad, Mahbuba; Shoja, Mohammadali M.; Ghabili, Kamyar
Abstract: Introduction : End-stage renal disease is the most debilitating condition for patients with renal diseases. Cardiovascular disease is the leading cause of death in these patients. It has been shown that nitric oxide (NO) increases in renal failure and hemodialysis patients and could be correlated with cardiovascular diseases in this population. Objectives : To investigate the relation between exhaled nitric oxide (eNO) and left ventricular performance in chronic hemodialysis patients. Methods : In this prospective study, eNO was measured in 20 chronic hemodialysis patients (13 males and 7 females with the mean age of 45.20 ± 14.99 years). Left ventricular findings were studied by conventional and Doppler echocardiography. eNO correlation with the echocardiographic parameters was evaluated. Results : The median eNO was 11.65 ppb (range: 1.9–29.9 ppb). eNO was positively correlated with left ventricular ejection fraction ( ρ  = 0.561, p =  0.01) and negatively correlated with left ventricular end systolic volume ( ρ  = −0.451, p =  0.046), isovolumic relaxation time ( ρ  = −0.448, p =  0.047) and myocardial performance index ( ρ  = −0.587, p =  0.007). Conclusion : There is a positive correlation between eNO and left ventricular performance in chronic hemodialysis patients. Therefore, eNO may play an important role in pathophysiology of cardiac involvement in these patients.